Conceptual Change - a new Research Task in TVET - Bauer, Waldemar [Verfasser] (My University, 2010)
"Under the common denominator of the conceptual change approach to learning, several theoretical assumptions have served as a source of hypotheses and have guided rich and fruitful research agendas in science education. Conceptual change research has shown that students have inituitive knowledge or conceptions of phenomena which are different from those of scientific conceptions. This research has provided detailed descriptions and explanations of learners' difficulties in diverse areas, such as physics or mathematics. Researchers developed a sample of theories in order to explain these initial conceptions and the process of its development. Most theories are dichotonomous; they divide the world into correct scientific concepts and erroneous naive concepts. The different meanings, its element and scope of concepts within a specific context of action are usually not in the focus of this type of research. This aspect is very relevant in studying domain-specific expertise and designing learning arrangements in TVET." (Autorenreferat, BIBB-Doku)
Keywords: T 2.2 Lerntheorien; Lerntheorie; Kompetenzerwerb